Modifying microstructure and mechanical properties of twin-wire directed energy deposition-arc (TW-DED-arc) fabricated Ti-48Al-2Cr-2Nb alloy via ultra-high frequency pulsed (UHFP) current - Jianwen Xin; Fang Li; Chen Shen; Lin Wang; Wenlu Zhou; Danqi Zhang; Yuelong Zhang; Dongsheng Wu; Xueming Hua (Materials & Design)
Twin-wire directed energy deposition-arc (TW-DED-arc) is an emerging technology specifically designed for additive manufacturing (AM) of intermetallics with low-cost and high efficiency. Especially in recent years, TW-DED-arc has proved its capability in fabricating Ti-48Al-2Cr-2Nb (TiAl-4822) with competitive mechanical properties compared to casting and electron beam powder bed fusion (EB-PBF). However, as an in-situ alloying based technique, the TiAl-4822 alloy fabricated via TW-DED-arc is challenged by micro-segregation of alloying elements and coarsening of lamellar structures, both of which are detrimental to mechanical properties and microstructure homogeneity. To effectively control these two issues thus further enlarge the processing window, the present work employs ultra-high frequency pulsed (UHFP) current into the plasma arc aiming to amplify the inhibitory effect of high currents on the micro-segregation, and meanwhile refining the full-lamellar grain structure. Obtained experimental results have indicated that compared to reference TiAl-4822 sample fabricated without UHFP current, with 15 A UHFP current of 20 kHz frequency, element segregation of Al is inhibited by 40 %, lamellar thickness of grain structure in top area is refined by 61 %, and the middle area structure by 23 %. Also, the discontinuous coarsened structures that appeared during high-current deposition were eliminated, leading to a significant improvement in the room temperature ultimate tensile strength of TW-DED-arc fabricated TiAl-4822 alloy by almost 15 %. In general, the UHFP current has proved its necessity being integrated into the TW-DED-arc system for TiAl-4822 alloy fabrication by suppressing element segregation, refining microstructure, and improving mechanical properties.